Exceptional educators: a collaborative training partnership for the inclusion of students with Down's syndrome. Issue 1 (February 2016) - Vaughan, Michelle; Henderson, Anne
Abstract : This article discusses the results of a teacher training initiative in the United States. Exceptional Educators is the result of an inter‐organisational collaboration between a community‐based organisation (Gold Coast Down Syndrome Organization), the local public school system and a university professor. The training focuses on three distinct objectives; understanding the physical and emotional needs of the disability, creating modified curriculum units based on individual learning goals and recognising common behavioral problems that arise in school settings. Overall, the results showed positive outcomes, with gains in knowledge of curriculum modification, behavioural strategies and overall understanding of Down's syndrome, as well as an increase in confidence level. A six‐week follow‐up survey indicated that the majority of the participants used the information presented back in their teaching environments. This study also investigated the added value of this collaboration, finding that the community connection often continues past the training and has provided teachers additional avenues for support.